Perbedaan nilai actual return, expected return, abnormal return, trading volume activity dan security return variability sebelum dan sesudah merjer pada perusahaan yang terdaftar di bursa efek Indonesia - FRESTIN CHRISNANTI (Jurnal Bisnis dan Akuntansi, 2015)
Merger activities constitute important information for shareholders. A merger activities announcement that is released by a company will influence the share price of acquiring company. This research aims to know how far merger could build positive impact to acquiring company. By examining this research, the author tried to know actual return, expected return, abnormal return, trading volume activity, and security return variability of share before and after merger since 2005 till 2010 at the companies listed in Indonesia Stock Exchange. This research used purposive sampling for defining the sample. The sample used in this research consists of 10 companies from various industries sector. This period of research was 60 days, divided into 30 days before merger and 30 days after merger. The result of this research is that there are no mean differences in actual return, expected return, abnormal return, and security return variability before and after merger activities. But there is a difference in trading volume activity before and after merger. The next research is suggested to be done by others evaluation method to measure the expected return.